2006
DOI: 10.1680/geot.2006.56.8.561
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory study of the development of earth pressure behind integral bridge abutments

Abstract: (2006) A laboratory study of the development of earth pressure behind integral bridge abutments. Geotechnique, 56 (8). pp. 561-571 Permanent WRAP URL: http://wrap.warwick.ac.uk/85236 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 12 publications
1
26
1
Order By: Relevance
“…These assemblies of steel spheres are an ideal material and are considered here to be an analogue soil. For example, this material has a geometry that is substantially simpler than the geometry of real sands (the importance of geometry on cyclic soil response is considered by Clayton et al, 2006), and this material will not exhibit the degree of particle abrasion under cyclic loading observed by Festag and Katzenbach (2001). The use of such an ideal material is in this study is motivated by a desire to directly compare simulations performed using the DEM model with physical test data for validation purposes.…”
Section: Test and Simulation Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These assemblies of steel spheres are an ideal material and are considered here to be an analogue soil. For example, this material has a geometry that is substantially simpler than the geometry of real sands (the importance of geometry on cyclic soil response is considered by Clayton et al, 2006), and this material will not exhibit the degree of particle abrasion under cyclic loading observed by Festag and Katzenbach (2001). The use of such an ideal material is in this study is motivated by a desire to directly compare simulations performed using the DEM model with physical test data for validation purposes.…”
Section: Test and Simulation Descriptionsmentioning
confidence: 99%
“…Cyclic loads of relatively high frequency are felt during earthquakes, however lower frequency repeated loadings are also important. Such loading scenarios include the foundations to road pavements (e.g., Lekarp et al, 2000), wind turbine foundations, foundations to reciprocating machines, soil adjacent to integral bridge abutments (e.g., Clayton et al, 2006), and soil in dams where the reservoir level ‰uctu-ates. Janbu and Seneset (1981) proposed that observed time-dependant settlements of structures on high permeability soils may be due to combined eŠects of cumulative displacements under cyclic loading and creep.…”
Section: Introductionmentioning
confidence: 99%
“…England and Dunstan (1994) also evaluated this intrinsic stress-strain property of sand to understand the mechanism of the buildup of the earth pressure by cyclic loading. The discussers (Clayton et al 2006;Xu et al 2007a) also performed stress path tests using a triaxial apparatus on a solid cylindrical specimen. The discussers call the 'cyclic strain-hardening effect' the 'grain-interlocking mechanism'.…”
Section: Physical Model Tests or Element Tests Or Bothmentioning
confidence: 99%
“…Although the particles of SLB sand are slightly smaller than those of the LB sand (fraction B) used by the discussers, both are similarly rather round (Figures 55b and 55c). Clayton et al (2006) and Xu et al (2007a) evaluated the effect of particle shape in stress path tests and found that, by cyclic loading with a fixed amplitude of lateral strain, the peak lateral stress in the respective cycles increases considerably, approaching the passive earth pressure for LB sand (fraction B), where this is not the case for a spherical uniformly graded granular material, glass ballotini. Although LB sand (fraction B) and SLB sand are not spherical, they are much more round than Toyoura sand ( Figure 55 and Table 2).…”
Section: Effect Of Particle Shapementioning
confidence: 99%
See 1 more Smart Citation